Improving Students' Reading Ability Through Retelling Technique - Susanti, Susanti; Nurhikmah, Nurhikmah (Pustaka Digital Indonesia, 2022)
The aim of this study was to improve reading skills on the competency standards for understanding short texts by reading aloud through the retelling technique of the first graders of SD Negeri Candimulyo 01. The approach used in this study was a quantitative approach, with the type of action research. In this study researchers collaborated with other teachers as well as with the principal. get accurate research results, the data that has been collected to be analyzed statistically, namely using the formula mean or average. Referring to the action hypothesis proposed in class 1 action research, totaling 16 students in pre-cycle average assessment 57.12 learning completeness results 30.11% increased 67.12 or 64.70% completeness in cycle I and cycle II increased to 76 .35 or 100% completeness. So, it can be concluded that there is an increase in reading ability through the retelling technique of class I students at SD Negeri Candimulyo 01. The novelty in this study is a concept of improving students' reading skills through a guide between constructivism and behaviorism theory through storytelling techniques in front of friends.